Impact of Charismatology and Pentecostalism on Third Millennial Christianity in Africa - Clement Chinkambako Abenguni Majawa (QUAERENS: Journal of Theology and Christianity Studies, 2025)
The Catholic Charismatic Renewal (CCR) has emerged as one of the fastest-growing movements within the universal Church, particularly in Africa. This article examines the biblical, ecclesiological, and social foundations of CCR in the context of third-millennium African Christianity. Drawing from Scripture, patristic tradition, Vatican II teachings, and African communal values, the article argues that CCR is not an alien import but a legitimate expression of the Church’s Pentecostal nature. The study employs a theological and socio-ecclesial analysis to demonstrate that the gifts of the Holy Spirit—when properly discerned and guided by Church authority—serve as effective means for personal renewal, deeper evangelization, and holistic societal transformation. The article concludes that Africa’s rich spiritual worldview and communal ethos provide fertile ground for an authentic, inculturated Charismatic spirituality that can contribute significantly to global Pentecostal and Charismatic Christianity. This research makes two original contributions to the scholarly discourse. First, it systematically synthesizes the biblical, ecclesiological, and social foundations of CCR within an integrated theological framework, filling a gap in the literature that has previously treated these three dimensions separately. Second, it offers an inculturation framework for CCR in Africa that respects local wisdom while preserving Catholic identity, thereby providing an original contribution to the global discourse on Pentecostalism and Charismatic movements in the Global South.